Optimalisasi Manajemen Rantai Pasok Untuk Pertumbuhan Berkelanjutan Petani Bunga Di Kopeng, Kabupaten Semarang - Pipit Sundari; Cahyani Tunggal Sari; Zumrotun Nafi’ah (CV. Multi Kreasi Media, 2024)
Optimizing supply chain management is a key factor in supporting sustainable growth, especially for flower farmers in Kopeng, Semarang Regency. This study aims to identify and implement effective supply chain management strategies to improve the welfare of flower farmers and support sustainable growth. The research method uses a participatory approach that actively involves flower farmers in all stages of the research, from problem identification, solution development, to evaluation of implementation results. Data were collected through in-depth interviews, focus group discussions, and field observations. The results of the study indicate that supply chain management in Kopeng faces several major challenges such as price fluctuations, limited market access, and lack of coordination between stakeholders. The proposed strategies to address these issues include strengthening farmer groups, utilizing information technology, product diversification, and implementing sustainable agricultural practices. The implementation of these strategies is expected to improve operational efficiency, farmer welfare, and environmental sustainability. This study makes a significant contribution to the literature on supply chain management in the agricultural sector and can be a reference for similar research in the future.